Multimodality Analysis: Visual Representation in Bli-Bli 12.12 and Lazada 12.12 TV Commercials - Kuntum Khaira Ummah; Hamzah Hamzah (Universitas Negeri Padang, 2022)
This study examines the different meaning in the visual analysis of Bli-Bli 12.12 and Lazada 12.12 advertisements. This study aims to determine the difference in meaning in visual analysis using the theory of reading images from Kress and Leeuwen (2006). Visual data analysis on these two advertisements is divided into three levels, namely representational, interactional, and compositional. The data is in the form of screenshots taken from the ad videos of bli-bli 12.12 and lazada 12.12. This research method uses descriptive qualitative research. The results showed some similarities and differences between the two advertisements in the theory of Reading images by Kress and Leeuwen (2006). The similarities in the visual data of the two advertisements can be seen in the dominance of advertisements by primary announcements and the difference in the different amounts of data in each part of the analysis point.